Virus-virus interactions alter the mechanical transmissibility and host range of begomoviruses - Chang, Ho-Hsiung; Gustian, Deri; Chang, Chung-Jan; Jan, Fuh-Jyh (Frontiers in Plant Science, 2023)
Begomoviruses are mainly transmitted by whiteflies. However, a few begomoviruses can be transmitted mechanically. The mechanical transmissibility affects begomoviral distribution in the field. In this study, two mechanically transmissible begomoviruses, tomato leaf curl New Delhi virus-oriental melon isolate (ToLCNDV-OM) and tomato yellow leaf curl Thailand virus (TYLCTHV), and two nonmechanically transmissible begomoviruses, ToLCNDV-cucumber isolate (ToLCNDV-CB) and tomato leaf curl Taiwan virus (ToLCTV), were used to study the virus-virus interaction on mechanical transmissibility. Co-inoculation was conducted on Nicotiana benthamiana and host plants through mechanical transmission with inoculants derived from plants that were mix-infected or derived from individually infected plants and the inoculants were mixed right before inoculation. Our results showed that ToLCNDV-CB was mechanically transmitted with ToLCNDV-OM to N. benthamiana, cucumbers, and oriental melons whereas ToLCTV was mechanically transmitted with TYLCTHV to N. benthamiana and tomatoes. For crossing host-range inoculation, ToLCNDV-CB was mechanically transmitted with TYLCTHV to N. benthamiana and its nonhost tomatoes while ToLCTV with ToLCNDV-OM to N. benthamiana and nonhost oriental melons. For sequential inoculation, ToLCNDV-CB and ToLCTV were mechanically transmitted to N. benthamiana plants which were either pre-infected with ToLCNDV-OM or TYLCTHV. Results of fluorescence resonance energy transfer analyses showed that nuclear shuttle protein of ToLCNDV-CB (CBNSP) and the coat protein of ToLCTV (TWCP) localized alone to nucleus. When coexpressed with movement proteins of ToLCNDV-OM or TYLCTHV, CBNSP and TWCP re-localized to both nucleus and cellular periphery and interacted with movement proteins. Our findings indicated that virus-virus interaction in mixed infection circumstances could complement the mechanical transmissibility of nonmechanically transmissible begomoviruses and alter their host range. These findings provided new insight into the complicated virus-virus interaction and will help us understand more about begomoviral distribution and reevaluate disease management strategy in the field.